Distillation design - Kister, Henry Z. (McGraw-Hill, 1992)
Introduction to distillation; Key fractionation concepts; Column process design, optimization, and shortcut calculations; Rigorous distillation calculations; Batch distillation; Tray design and operation; Tray efficiency; Packing design and operation; Packing efficiency and scaleup; Packing capacity and pressure drop GPDC interpolation charts atlas; Packing efficiency data.